Penerapan konsep istihalah pada hukum vaksin measles rubella: Analisis hukum dalam pandangan imam madzhab - Rouf, Abd. (LP3M Universitas Islam Zainul Hasan Genggong, 2024)
The majority of Muslim intellectuals are of the opinion that seeking medical treatment is obligatory. This is different when it comes to the consumption of medicine from a haram element. Currently, there is much debate about the measles rubella vaccine (MR-vaccine) regarding the legality of its use according to Shara' because it contains pork and human organs. Considering that the Minister of Health will provide the MR-vaccine for newborns (immunity), the Indonesian Ulema Council (MUI) issued a haram fatwa against the MR-vaccine, but it becomes permissible with the principle of sharia rules, namely dharurat. According to researchers, this is ambiguous in taking legal formulation. Whereas there is the concept of Istihalah in making the MR-vaccine which makes a haram element halal. This research is a descriptive-qualitative research, using the literature method with a tarjih approach, and using primary and secondary data in the research. This research produces: First, the rubella vaccine is legal even though it contains pork or human organs, not because of the element of emergency, but it has changed from the original haraam form to something else, both from the dzatiyah and nature. Second, the concept of istiḥalah using the al-tafa'ul al-kimiyawa method is the strongest basis for stating that the rubella vaccine is halal and pure.